The Graeco-Bactrian and Indo-Greek world - Mairs, Rachel (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This volume provides a solid grounding in the field of Graeco-Bactrian and Indo-Greek studies, mixing theoretical and historical surveys with critical and thought-provoking case studies and in archaeology, history, literature and art. The chapters from this international group of experts showcase innovative methodologies, such as archaeological GIS, as well as providing accessible explanations of specialist techniques such as die studies of coins, as well as important theoretical perspectives, including postcolonial approaches to the Greeks in India. Chapters cover the region's archaeology, written and numismatic sources, and a history of scholarship of the subject, as well as culture, identity and interactions with neighbouring peoples, including China. The Graeco-Bactrian and Indo-Greek World is the go-to reference work on the field, and fulfils a serious need for an accessible, but also thorough and critically-informed, volume on the Graeco-Bactrian and Indo-Greek kingdoms. It provides an invaluable resource for anyone interested in the Hellenistic Greek East"--
Section 1. Interactions -- Section 2. History of scholarship -- Section 3. Regional archaeological survey -- Section 4. Written sources -- Section 5. Numismatic sources -- Section 6. Culture and identity -- Section 7. Beyond the Graeco-Bactrian and Indo-Greek worlds.
OCLC-licensed vendor bibliographic record.
Keywords: Greeks -- Asia, Central -- History; Indo-Greeks -- History; Coins, Greek -- Asia, Central; Coinage -- Asia, Central -- History; Bactria -- Antiquities; Asia, Central -- Antiquities; India -- Antiquities; HISTORY / Ancient / General